2018
DOI: 10.20944/preprints201806.0156.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emissions from the Road Traffic of West Africa’s Cities: Assessment of Vehicle Fleet and Fuel Consumption

Abstract: Traffic source emissions inventories for the rapidly growing West African urban cities are necessary for better local characterization of vehicle emissions released into these cities atmosphere. This study based on local field campaign in a representative site of anthropogenic activities over West African cities such as Yopougon (Abidjan, Côte d'Ivoire) during 2016, provided useful information on vehicle type and age, traveling time, fuel type and amount for fuel consumption estimation. Also, high tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…7 However, several studies have shown that some genotypes of D. alata have the ability to form good dough, comparable to that of D. rotundata. 8,9 The importance of yams in terms of food security has led to the establishment of several genetic improvement programs for D. alata throughout the tropical regions, in order to develop new varieties with high yield, good food quality and resistance to pests and diseases. 3,[10][11][12][13] Sensory quality evaluations of new genotypes are mostly carried out using sensory panels.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, several studies have shown that some genotypes of D. alata have the ability to form good dough, comparable to that of D. rotundata. 8,9 The importance of yams in terms of food security has led to the establishment of several genetic improvement programs for D. alata throughout the tropical regions, in order to develop new varieties with high yield, good food quality and resistance to pests and diseases. 3,[10][11][12][13] Sensory quality evaluations of new genotypes are mostly carried out using sensory panels.…”
Section: Introductionmentioning
confidence: 99%